2015
DOI: 10.3126/ijasbt.v3i1.11849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integration of Organic and Inorganic Sources of Nitrogen on Growth, Yield and Nutrient Uptake by Maize (Zea mays L.)

Abstract: A field study was conducted at Agronomy Research Farm of Punjab Agricultural University during kharif 2013 to evaluate the effect of organicand inorganic sources of nitrogen on maize. Experiment was laid out in split plot design with four replications comprising three farmyardmanure levels (0, 15 and 20 t/ha) in main-plots and five nitrogen levels 0, 75, 100, 125 and 150% of recommended dose (125 kg/ha) throughinorganic fertilizer in sub-plots. Plant growth and yield characters and nutrient content as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
(5 reference statements)
2
9
0
Order By: Relevance
“…However, the minimum values of N content of shoot and roots were obtained in control at all the stages of the rice crop, respectively. Similar results have been reported by Qiao-Gang et al [10]; Kafle and Sharma [11]; Senthilvalavan and Ravichandran [12]; Singh (2017). Earlier, Quingling et al [13] reported that higher N significantly increased by dry matter partitioning of the leaf at the vegetative stage.…”
Section: Nitrogen Partitioningsupporting
confidence: 91%
“…However, the minimum values of N content of shoot and roots were obtained in control at all the stages of the rice crop, respectively. Similar results have been reported by Qiao-Gang et al [10]; Kafle and Sharma [11]; Senthilvalavan and Ravichandran [12]; Singh (2017). Earlier, Quingling et al [13] reported that higher N significantly increased by dry matter partitioning of the leaf at the vegetative stage.…”
Section: Nitrogen Partitioningsupporting
confidence: 91%
“…The amount of fertiliser applied is responsible for the amount of nitrogen, phosphorus and potassium uptake in maize. The increase in P and K uptake was due to the fact that nitrogen promotes phosphorus and potassium uptake by increasing top and root growth, altering plant metabolism and increasing P and K solubility and availability Kafle et al, (2016). Among the treatments, STCR-IPNS treatment with STCR-IPNS-200 % FD for 5 t ha-1 +FYM @ 12.5 t ha -1 (T10) recorded significant and the highest total uptake of N 241.82 kg ha -1 (Table 2).…”
Section: Grain and Stover Yieldmentioning
confidence: 99%
“…Nitrogen is an essential constituent of chlorophyll. An adequate supply of N might result in high photosynthetic activity and vigorous vegetative growth (Kafle and Sharma 2015). Mitova et al (2017) have found that the chlorophyll content in two varieties of lettuce was affected significantly by the mycorrhizal fungi inoculation, but much higher values were observed in one of these varieties compared to the other.…”
Section: Discussionmentioning
confidence: 99%